(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The article examines the phenomenon of ecumenism as a dynamic reality that has evolved from the idea of church unity into a contemporary model of interconfessional and interreligious interaction. The study analyzes the historical and theological premises for the emergence of the ecumenical movement and highlights the impact of social, cultural, and political factors on its development in the twentieth and twenty-first centuries. Particular attention is paid to the processes of institutionalization of ecumenism, its transformation into a stable form of religious cooperation, and the adaptation of universal principles of Christian dialogue to specific regional traditions. The article emphasizes the significance of ecumenism as a factor in strengthening a culture of religious tolerance, civil peace, and spiritual solidarity in contemporary society.